Conservation of the 17-Kilodalton Antigen Gene within the Genus Bartonella - Sweger, Debra (American Society for Microbiology, 2000)
The 17-kDa antigen of Bartonella henselae has previously been shown to elicit a strong humoral immune response in patients with cat scratch disease (CSD) and to be useful in screening human serum samples for CSD. In this study, PCR amplification of genes homologous to the 17-kDa antigen gene of B. henselae was performed using genomic DNAs from several species of Bartonella, including the currently recognized human pathogens. Amplicons of similar size were demonstrated using the following chromosomal DNA templates: B. henselae (two strains), B. quintana (two strains), B. elizabethae, B. clarridgeiae, B. vinsonii subsp. vinsonii, and B. vinsonii subsp. berkhoffii. No evidence of a B. bacilliformis homolog of the 17-kDa antigen gene was obtained using multiple primer pairs. DNA sequencing revealed open reading frames capable of coding for proteins with sizes similar to that of the 17-kDa antigen of B. henselae in all of the amplicons; however, extensive sequence divergence across the genus was noted. Cloning of the amplified products into pUC19 resulted in recombinants that directed synthesis of homologs of the 17-kDa protein. Immunoblot analysis using human sera from CSD cases demonstrated very little cross-reactivity among different species for this protein. In contrast, immunoblots using rabbit serum raised to the recombinant B. henselae antigen showed extensive cross-reactivity with the proteins of other Bartonella species. The data suggest that the use of the 17-kDa antigen as a serologic reagent may allow the development of more specific diagnostic assays. Furthermore, the nucleotide sequences from the various versions of the 17-kDa antigen gene should be useful for rapid identification of Bartonella at the species level.